Comparisons of countermovement jump force profiles in youth athletes - Gillen, Z. M.; McHugh, M. P.; Shoemaker, M. E.; Cramer, J. T. (Translational Sports Medicine, 2021)
The purposes of this study were to determine whether countermovement jump (CMJ) force profiles differ for jumps in which peak force occurred at the low position of the countermovement (LP) compared to jumps in which peak force did not occur at the low position of the countermovement (NLP), and compare relationships among CMJ and isokinetic metrics between groups. Thirty-nine male and female youth athletes between 9- and 17-year-old participated. Participants completed CMJs and isokinetic knee extensions from 60 to 300°·s-1. Ground reaction forces were collected during CMJs to quantify unweighting, braking, propulsive, and performance metrics. Torque and power were quantified during all isokinetic knee extensions. Forty-one percent of participants had LP force profiles, while 59% of participants had NLP force profiles. The LP group had more efficient unweighting and braking phase metrics than the NLP group, while the NLP group had greater isokinetic torque and power, and greater relationships between CMJ and isokinetic metrics, than the LP group. CMJs from the LP group represent more biomechanically efficient jumps than CMJs from the NLP group. Additionally, the NLP group may be more reliant on concentric force production during the CMJ, while the LP group may have more efficient storage and utilization of elastic energy.